In vitro and in vivo suppression of SARS‐CoV‐2 replication by a modified, short, cell‐penetrating peptide targeting the C‐terminal domain of the viral spike protein. Issue 3 (7th March 2023) - Kim, Dongbum; Kim, Jinsoo; An, Seungchan; Kim, Minyoung; Baek, Kyeongbin; Kang, Bo Min; Maharjan, Sony; Kim, Suyeon; Hwang, Seok Young; Park, In Guk; Park, Sangkyu; Suh, Jun Gyo; et al.
Abstract: Peptides are promising therapeutic agents for COVID‐19 because of their specificity, easy synthesis, and ability to be fine‐tuned. We previously demonstrated that a cell‐permeable peptide corresponding to the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Spike C‐terminal domain (CD) inhibits the interaction between viral spike and nucleocapsid proteins that results in SARS‐CoV‐2 replication in vitro. Here, we used docking studies to design R‐t‐Spike CD(D), a more potent short cell‐penetrating peptide composed of all D‐form amino acids and evaluated its inhibitory effect against the replication of SARS‐CoV‐2 S clade and other variants. R‐t‐Spike CD(D) was internalized into Vero cells and Calu‐3 cells and suppressed the replication of SARS‐CoV‐2 S clade, delta variant, and omicron variant with higher potency than the original peptide. In hemizygous K18‐hACE2 mice, intratracheal administration of R‐t‐Spike CD(D) effectively delivered the peptide to the trachea and lungs, whereas intranasal administration delivered the peptide mostly to the upper respiratory system and stomach, and a small amount to the lungs. Administration by either route reduced viral loads in mouse lungs and turbinates. Furthermore, intranasally administered R‐t‐Spike CD(D) mitigated pathological change in the lungs and increased the survival of mice after infection with the SARS‐CoV‐2 S clade or delta variant. Our data suggest that R‐t‐Spike CD(D) has potential as a therapeutic agent against SARS‐CoV‐2 infection.